If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6f-1=4f-1
We move all terms to the left:
6f-1-(4f-1)=0
We get rid of parentheses
6f-4f+1-1=0
We add all the numbers together, and all the variables
2f=0
f=0/2
f=0
| 14=3+b=8 | | x+53=x+57 | | 4(5-2x)+3=7 | | 434=38x+54 | | -3x^2+35x-100=3x-36+x^2 | | F(3)=-3x+10 | | 4f(-3)=-3^2-5(-3)+1 | | 6(x-3)+2x=38 | | 101=-7b+10 | | 14(20s+25)+20=-5(-59s-75)+10s | | h-84/5=2 | | -7x+-8=-10x+4 | | –2x+14=x–14 | | d/9.7=20.3 | | 3x+2(x-5)=35 | | -8(3m)=79 | | 3x+6+2x+130-x=180 | | 0.10(y-6)+0.43y=0.03y-0.40 | | 28=24+w=2 | | q/6-1=2 | | 4(2p-2)-7=p+13 | | 4.7p=18.8 | | 7(-16g+13)+14=-7(11g-13)+35 | | 10x+8-7x=23 | | 7x+1+7x+6=180-15x | | 10+2x=2+6x | | 6(y-85)=6 | | (0.5y+0.4)=5(0.1y+1.3)+1.3 | | -7(x+8)=-14 | | 28f=616 | | 3(4x+9)=19x+22-7x+5 | | n8+16=64 |